IDENTIFIKASI BAKTERI Vibrio sp DALAM HEPATOPANKREAS UDANG VANNAMEI (Litopenaeus vannamei ) PADA TAMBAK YANG DIBERI PROBIOTIK DI TAMBAK SAMPANG TIGO KELURAHAN DEGAYU KOTA PEKALONGAN - Ike Fatmala; Hadi Pranggono; Linayati Linayati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2019)
Shrimp vannamei (Litopenaeus vannamei) is a kind of shrimp that has important economic value in Indonesia, one of the inhibiting factors in increasing shrimp production is a disease caused by bacteria vibrio sp. This disease can cause a high death. This study aims to identify and quantify the number of Vibrio sp bacteria colonies in the hepatopancreas shrimp vannamei in ponds given probiotics, carried out in Sampang Tigo Ponds, Degayu –Pekalongan and Central Fish Ponds Brackish Water Aquaculture (BBPBAP), Jepara. This study was conducted on Monday 13 November 2017 to Wednesday April 25 2018. The study was conducted on a pond with a density of 100 and 116 tail / m3. The data of the research results were analyzed descriptively with the help of graphs and tables. The results showed that the sample of each plot of bacterial colonies exceeded the threshold, that is the average number of vibrio sp bacterial colonies on hepatopancreas shrimp T2 3,96 x 10 6 CFU/ml and T3 plots 1,46 x 10 6 CFU/ml followed by shrimp morphological changes that have clinical signs of vibrio sp bacteria, the state of unbalanced water quality supports the bacterialgrowth. Keywords: Cultivation, Vannamei shrimp, Vibrio sp, Density